Duodenal obstruction due to a preduodenal portal vein - MNC Vilakazi; F Ismail; H M Swanepoel; E W Muller; Z I Lockhat (Wolters Kluwer Medknow Publications, 2014)
An infant presented with clinical signs and symptoms suggestive of a pyloric stenosis. On abdominal ultrasound, pyloric stenosis was excluded, and other causes for proximal duodenal obstruction, such as a duodenal web or annular pancreas, were suspected. At surgery, the cause was found to be due to an anterior portal vein or preduodenal portal vein, compressing the duodenum. There were no associated findings such as midgut malrotation, duodenal web and congenital anomalies. The treatment was a diamond-shaped duodeno-duodenostomy anterior to the portal vein. The patient improved after surgery.